Tettigoniinae (Orthoptera: Tettigoniidae) from Turkey with key to genera and descriptions of six new species - Ünal, Mustafa (Zootaxa, 2018)
The third part of a study series on the family Tettigoniidae from Turkey and the Middle East Region is presented, which includes only the subfamily Tettigoniinae of Turkey. A key to tribes, genera and subgenera found in Turkey is proposed. The synonymy of the tribe Platycleidini Brunner, 1893 (with Decticini Herman, 1874) is confirmed. Pezodrymadusa striolata ziyaretensis Koçak & Kemal, 2010 [with Pezodrymadusa affinis (I.Bolívar, 1899)], Anadolua rammei Karabağ, 1952 (with Anadolua burri Karabağ, 1952), Psorodonotus rize Kaya et Çıplak, 2014 (with Psorodonotus davisi Karabağ, 1956), Parapholidoptera intermixta Karabağ, 1961 [with Parapholidoptera indistincta (I.Bolívar, 1899)] are synonymized. Parapholidoptera indistincta (I.Bolívar, 1899) is reinstated as an independent species. Six new species, Pezodrymadusa dentata Ünal, sp. nov., Mixodusa retusa Ünal, sp. nov., Platycleis (Squamiana) supericola Ünal, sp. nov., Platycleis (Squamiana) goeksunica Ünal, sp. nov., Parapholidoptera yarpuzi Ünal, sp. nov. and Eupholidoptera singularis Ünal, sp. nov. are described. The invalidly described Schulmeisteri schulmeisteri Harz is discussed and its only specimen is included in the genus Pezodrymadusa as a new species. The genus Mixodusa Stolyarov and the subspecies, Pholidoptera aptera bulgarica Maran, 1953 are recorded from Turkey for the first time. An overlooked historical record of Psorodonotus venosus brunneri Stshelkanovtzev, 1914 from Turkey is determined. Discussions of many taxa and some records from new localities are presented. A full list of the Turkish Tettigoniinae is given. 357 figures are provided.